Age Trends in Actigraphy and Self-Report Sleep Across the Life Span: Findings From the Pittsburgh Lifespan Sleep Databank. Issue 4 (28th May 2022) - Wallace, Meredith L.; Kissel, Nicholas; Hall, Martica H.; Germain, Anne; Matthews, Karen A.; Troxel, Wendy M.; Franzen, Peter L.; Buysse, Daniel J.; Reynolds, Charles; Roecklein, Kathryn A.; Gunn, Heather E.; Hasler, Brant P.; et al.
Abstract : Using individual-level cross-sectional data from the Pittsburgh Lifespan Sleep Databank, we characterized age trends and sex differences in actigraphy and self-report sleep dimensions across the healthy human life span. Our analyses revealed age trends that differed by modality and sleep dimension. Awareness of age trends in multiple sleep dimensions in healthy individuals can suggest periods of sleep-related risk or resilience and guide intervention efforts. ABSTRACT: Objective: Sleep changes over the human life span, and it does so across multiple dimensions. We used individual-level cross-sectional data to characterize age trends and sex differences in actigraphy and self-report sleep dimensions across the healthy human life span. Methods: The Pittsburgh Lifespan Sleep Databank consists of harmonized participant-level data from sleep-related studies conducted at the University of Pittsburgh (2003–2019). We included data from 1065 ( n = 577 female; 21 studies) Pittsburgh Lifespan Sleep Databank participants aged 10 to 87 years without a major psychiatric, sleep, or medical condition. All participants completed wrist actigraphy and the self-rated Pittsburgh Sleep Quality Index. Main outcomes included actigraphy and self-report sleep duration, efficiency, and onset/offset timing, and actigraphy variability in midsleep timing. Results: We used generalized additive models to examine potentially nonlinear relationships between age and sleep characteristics and to examine sex differences. Actigraphy and self-report sleep onset time shifted later between ages 10 and 18 years (23:03–24:10 [actigraphy]; 21:58–23:53 [self-report]) and then earlier during the 20s (00:08–23:40 [actigraphy]; 23:50–23:34 [self-report]). Actigraphy and self-report wake-up time also shifted earlier during the mid-20s through late 30s (07:48–06:52 [actigraphy]; 07:40–06:41 [self-report]). Self-report, but not actigraphy, sleep duration declined between ages 10 and 20 years (09:09–07:35). Self-report sleep efficiency decreased over the entire life span (96.12–93.28), as did actigraphy variability (01:54–01:31). Conclusions: Awareness of age trends in multiple sleep dimensions in healthy individuals—and explicating the timing and nature of sex differences in age-related change—can suggest periods of sleep-related risk or resilience and guide intervention efforts.